ANALISIS PENGARUH ATRIBUT EKSTRINSIK TERHADAP HARGA TEH HITAM INDONESIA BERDASARKAN MODEL HARGA HEDONIK - , MIKA MARGARETA; , Dr. Ir. Dyah Ismoyowati., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
As heterogeneous product, the expectation price development of black tea to find the optimal price is difficult to be determined. Through the hedonic price as the willingness to pay of consumer on black tea can be known as the implicit price which can be used as a reference for price determination. The objectives of this research were to identify the influence of extrinsic attributtes on Indonesian black tea prices and to determine strategies PTPN and PT. KPBN consider in to increasing tea price based on consumer preferences. The studied characteristics were extrinsic attributes that offered in Jakarta Tea Auction (company, garden, and grade) from weekly data recapitulation of auction result and organoleptic datas during 2012. Logistic regression was applied in this study. The results showed that the extrinsic attributes which affected the price of black tea above its average and its influence degree were (i) company PTPN VIII : 7,01, (ii) garden Walini : 6,70